STUDI PELKASANAAN PENYULUHAN PERTANIAN PASCA PEMBERIAN BIAYA OPERASIONAL PENYULUH PERTANIAN (BOP) (STUDI KASUS KABUPATEN SUKABUMI PROVINSI JAWA BARAT) - Zahron Helmy (Universitas Sebelas Maret, 2007)
Agriculture development cannot go well except that supported by existence of systems of agriculture extension. agriculture extension represent the effort to develop ability, knowledge, skill and farmer attitude with their famuily and other stake holder passing study process so that will be and able to help and also him self organization, owning to access information source, technological and other resource to work along mutual profitable in solving problem faced, so that they can improve the productivity, efficiency business, earnings and prosperity